A diagnostic evaluation of single screen testing for malaria in the returning traveler: A large retrospective cohort study. (27th February 2021) - Reynard, Charles; Geary, Katie; Chiodini, Peter; Brereton, Michelle; Burthem, John; McDermott, John; van den Berg, Patricia; Body, Richard
Abstract: Background: Screening for malaria in the returning traveler has often required repeat testing; however, audit data suggest that patients have not been reattending. We sought to ascertain if this was safe by examining the diagnostic efficacy of a single screen consisting of a rapid diagnostic test (RDT) and a thin film. Methods: We conducted a retrospective cohort study of patients with suspected malaria who attended in the past 5 years from two large teaching hospitals. We assessed the diagnostic accuracy of a single screen, reporting measures of sensitivity and specificity. To establish a reference standard, we cross‐linked data with the national malaria registry held at Public Health England and regional centers. Results: The cohort consisted of 1365 patients, of whom 33 opted out of the research and one did not have a complete initial screen. Of those 1331 screens there were 74 cases of Plasmodium falciparum (prevalence of 5.6%) and 104 of any malaria species (prevalence of 7.8%). Sensitivity for the detection of P. falciparum was 100.00% (95% confidence interval [CI] = 95.1 to 100), with a specificity of 99.4% (95% CI = 98.9 to 99.8). For the detection of any species of malaria the sensitivity was slightly lower due to the presence of one false negative; sensitivity was 99.0% (95% CI = 94.8 to 100) and specificity was 99.5% (95% CI = 98.9 to 99.8). Conclusions: A single thin film and RDT is likely to be sufficient as a first screen for falciparum malaria in the returning traveler with important caveats. For those sent home from emergency departments, appropriate safety netting must be provided. Further prospective study is required to investigate this approach.